2017
DOI: 10.1186/s12885-017-3272-y
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 in lung adenocarcinoma: cross-sectional genetic and serological study

Abstract: BackgroundMucin 1 (MUC1) contributes to the growth and metastasis of various cancers, including lung cancer, and MUC1 gene length polymorphisms are associated with susceptibility to lung cancer and its prognosis. In contrast, the association between rs4072037, a single nucleotide polymorphism in MUC1, and lung cancer has not been well studied.MethodsIn the present study, we determined the rs4072037 genotype and measured serum KL-6 levels to evaluate the association between lung adenocarcinoma (ADC) and rs40720… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Histological analyses confirmed that these three patients were lung adenocarcinomas ( Table S1 ). Different biomarkers confirmed the general equivalence of primary biopsy and vascularized PDTs, and hence the good overall reliability of the proposed model: TTF-1, 29 cytokeratin-7 (CK-7 or KRT7), 30 and mucin-1 (MUC-1) 30 for lung adenocarcinoma-associated markers and Ki-67 for cell proliferation ( Figure 2 , See also Figure S1 ). Besides those typical lung adenocarcinoma-associated markers, we also checked for epithelial to mesenchymal transition markers, such as the expression of vimentin or the loss of E-cadherin.…”
Section: Resultssupporting
confidence: 56%
“…Histological analyses confirmed that these three patients were lung adenocarcinomas ( Table S1 ). Different biomarkers confirmed the general equivalence of primary biopsy and vascularized PDTs, and hence the good overall reliability of the proposed model: TTF-1, 29 cytokeratin-7 (CK-7 or KRT7), 30 and mucin-1 (MUC-1) 30 for lung adenocarcinoma-associated markers and Ki-67 for cell proliferation ( Figure 2 , See also Figure S1 ). Besides those typical lung adenocarcinoma-associated markers, we also checked for epithelial to mesenchymal transition markers, such as the expression of vimentin or the loss of E-cadherin.…”
Section: Resultssupporting
confidence: 56%
“…1). For memory, TTF-1 is a marker for epithelial-mesenchymal transition, used concomitantly with Ki-67, a marker of cell proliferation 22 , and with cytokeratin-7, and mucin-1, as predictive markers of tumor growth and metastasis 23,24 . All samples were negative for p40, the sensitive and speci c marker for distinguishing lung squamous cell carcinoma from adenocarcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, oncogene activated AT2s show disorganized apical domains, increasingly becoming unipolar at later stages, suggesting that the multi-apical polarity of AT2s is dynamically regulated in normal as well as disease states. Indeed, genetic mutations or altered expression of MUC1 has been implicated in lung cancer growth, metastasis, and chemotherapy resistance ( Bouillez et al., 2016 ; Ham et al., 2016 ; Horimasu et al., 2017 ; Raina et al., 2011 ; Saltos et al., 2018 ). In sum, our study has uncovered a unique multi-apical polarity of an epithelial cell type and its dynamics during development, injury repair, and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%